Glutathione S-Transferase May Contribute to the Detoxification of (S)-(−)-Palasonin in Plutella xylostella (L.) via Direct Metabolism - Qiqi Fan; Jiyuan Liu; Yifan Li; Yalin Zhang (Insects, 2022)
The control of P. xylostella primarily involves chemical insecticides, but overuse has brought about many negative effects. Our previous study reported that (S)-(−)-palasonin (PLN) is a plant-derived active substance with significant insecticidal activity against P. xylostella. However, we noticed a possible cross-resistance between (S)-(−)-palasonin and other insecticides which may be related to metabolic detoxification. In order to further explore the detoxification effect of detoxification enzymes on (S)-(−)-palasonin in P. xylostella, the effects of (S)-(−)-palasonin on enzyme activity and transcription level were determined, and the detoxification and metabolism of GSTs on (S)-(−)-palasonin were studied by in vitro inhibition and metabolism experiments. During this study, GST enzyme activity was significantly increased in P. xylostella after (S)-(−)-palasonin treatment. The expression levels of 19 GSTs genes were significantly increased whereas the expression levels of 1 gene decreased. Furthermore, (S)-(−)-palasonin is shown to be stabilized with GSTs and metabolized GSTs (GSTd1, GSTd2, GSTs1 and GSTs2) in vitro, with the highest metabolic rate of 80.59% for GSTs1. This study advances the beneficial utilization of (S)-(−)-palasonin as a botanical pesticide to control P. xylostella in the field.